RITUAL ISLAM DALAM MOTIF BATIK BESUREK-BENGKULU - Rizali Nanang (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
Batik has many roles and functions in the rule of its society. Oneof it is the batik functions in the social-religion activity. In Java, it is true that batik has ritual function in the early time. Previously, batik is one of king’s cloth. Batik with parang motif is worn only for the king in the formal ceremony as a symbol of legitimation. Since 20th century, batik has gone out from the Javanese palace and spread over territories around Nusantara. One of the places is Bengkulu Province which has special batik motive called batik besurek. The early literature didn’t identify besurek batik, but today it becomes one of the Bengkulu province icons. Besurekbatik has meaning in the Islamic ritual as one artefact used in funeral activity, tabut tradition, and circumcision ritual. The wearing of besurek batik is a way promote Islamic mission (dakwah). It is the way to glory the God (Allah). Recently, the people removed the verses Al-Qur’an written in Besurek batik and they changed the God verses with calligraphy that looks like Arabic alphabets without meaning called besurek.